Ethical Considerations in Online Business: A Comprehensive Literature Review - Hana Yunita Makhfudotin; Noor Fatimah Mediawati; Suyo Gigih Prasetyo (Proceedings of The ICECRS, 2023)
This data article presents a meticulously curated dataset aimed at simplifying digital forensic research in the domain of online business and social media. The study commences with a keyword-based search on Lens.org, yielding a total of 107,879 records, which are then exported in both CSV and BIBTEX formats. Subsequently, the dataset is refined by applying filters for "Journal Article" and "Conference Proceedings Article," resulting in 86,266 data entries. Finally, a filter for "Law" as the subject matter narrows the dataset down to 3,075 records. This comprehensive dataset serves as a valuable resource for researchers, facilitating literature reviews and enabling experimentation in the dynamic intersection of online business and social media, particularly in the context of legal aspects.Highlights : Comprehensive dataset creation for digital forensic research. In-depth exploration of online business and social media in the legal context. Facilitating future research, literature reviews, and experimentation. Keywords:Digital Forensics, Online Business, Social Media, Dataset, Legal Research